Studi konsiderasi agama dan budaya tentang etik dan emik terhadap implementasi sistim ekonomi Islam di Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Ahmad Abib Albajuri (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2020)
Two central aspects of culture are frequently discussed in the cross-cultural literature: the ethical aspect and the emic aspect. The objectives of this study are: 1) To find out whether Ethics and Emik simultaneously influence the implementation of the Islamic economic system 2) To find out whether Ethics and Emik partially influence the implementation of the Islamic economic system 3) To find out which of the two has the dominant influence among Ethics and Emik on the implementation of the Islamic economic system. This research is included in quantitative correlational research by following an exploratory, descriptive and explanatory research design. The primary data in this study were collected by the author through the distribution of research questionnaires. Collecting data using questionnaires, observation and documentation. The population of this study were the people of the Pacet village who became the recitation congregation and the recitation community in the shelter of the Riyadlul Jannah Pacet Mojokerto Islamic boarding school, totaling 4821 people. sampling using the Slovin formula with a significance level of 0.01 so that the sample was determined to be 98. The data analysis technique used multiple linear regression with the SPSS program. V. 26.0. From the research results, it can be concluded as follows: 1) Ethics and Emik simultaneously have a significant effect on the implementation of the Islamic economic system at Riyadlul Jannah Pacet Mojokerto Islamic Boarding School. 2) Ethics and Emik partially influence the implementation of the Islamic economic system at the Riyadlul Jannah Pacet Mojokerto Islamic Boarding School. 3) Emik has the most dominant (tight) influence on Ethics on the implementation of the Islamic economic system at Riyadlul Jannah Pacet Mojokerto Islamic Boarding School.